Assessment of Composite Restorations and Their Unique Features in Forensic Identification of Unidentified Human Beings - Ghodousi, A; Maleki, Z; Talebzadeh, E; Etemadi, Sh (International Journal of Medical Toxicology and Forensic Medicine, 2016)
Background: Dental identification mainly involves the comparison of antemortem and postmortem records. Keiser-Nielson (1980) recommended restored tooth surfaces as the smallest unit to consider in the comparison of dental restorations for identification purposes. Unique appearance of radiographic images of amalgam has led to their application in dental forensic. The present study aimed to investigate the value of composite restorations and their features in forensic identification. Methods: The antemortem sample included 40 periapical radiographs of anterior teeth with class III composite restorations which had been taken at least one year before the study. Ten randomly selected recent radiographs of the same subjects along with two radiographs from other patients were regarded as postmortem samples. Afterward, 12 dentally trained examiners were asked to match the 12 radiographs of group 2 with those of group 1 and to determine which features of the teeth (e.g. shape, contour, and surface) had helped them. Results: Ten examiners were able to correctly match all of the 12 images. According to kappa coefficient, the inter-rater agreement was high (0.8-1.0). The shape of the restoration was the most useful feature in identification. Conclusion: A composite restoration has a unique radiographic morphology that can be used for human identification. Therefore, if the antemortem radiograph of a single composite restoration is available, its comparison with a postmortem radiograph can help identify unidentified human beings.